Rehabilitation Engineering 2009
DOI: 10.5772/7383
|View full text |Cite
|
Sign up to set email alerts
|

Processing Surface Electromyographical Signals for Myoelectric Control

Abstract: Population ageing has major consequences and implications in all areas of our daily life as well as other important aspects, such as economic growth, savings, investment and consumption, labour markets, pensions, property and care from one generation to another. Additionally, health and related care, family composition and life-style, housing and migration are also affected. Given the rapid increase in the aging of the population and the further increase that is expected in the coming years, an important probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In the last decades, experiments on active prosthetics based on surface electromyography (sEMG) signals have increased significantly. Such experiments aimed to increase functionalities by using multichannel sEMG signals and to decrease the total response time [1][2][3][4]. Hence, active prosthetics will be more intuitive and possess close functionalities from the limbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, experiments on active prosthetics based on surface electromyography (sEMG) signals have increased significantly. Such experiments aimed to increase functionalities by using multichannel sEMG signals and to decrease the total response time [1][2][3][4]. Hence, active prosthetics will be more intuitive and possess close functionalities from the limbs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an experiment conducted by Khokhar et al [1] showed that the sEMGbased system can classify movement commands after detecting sEMG signals with high accuracy (up to ±96%) and a short total time response (250 ms). Figure 1 illustrates the general block diagram of sEMG-based active prosthetics: (a) general diagram block of active prosthetics for controlling its velocity; (b) a general block diagram of active prosthetic controlling its velocity and functionality [4]. Kirchner et al developed another method to shorten the total time response of active prosthetics [5].…”
Section: Introductionmentioning
confidence: 99%
“…In measuring the neural drive of muscles it is common practice to convert the raw EMG into a form more convenient for further analysis. Features may be computed in several domains, such as time domain, frequency domain, time-frequency and time-scale representations [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The classification is based on features for each type of movement. These features may be computed in several domains, such as time domain, frequency domain, timefrequency and time-scale representations (Herle and Man [2009]; Parker et al [2006] Time-frequency domain features show better performance than other-domain features in case of assessing transient properties of a signal. The central concept of most of the methods is a decomposition of a signal into time-frequency atoms:…”
Section: Introductionmentioning
confidence: 99%